PENGARUH KEBIJAKSANAAN PERUSAHAAN TERHADAP SEMANGAT DAN KEGAIRAHAN KERJA KARYAWAN - ARIFIN . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
This study aims to determine the wisdom in addition to the company as well as to determine the influence of company policy, namely: the provision of salary or wages, proper staffing, work environment, provision of facilities and incentives to the spirit and enthusiasm of employees at PT. Borneo Oil Kusuma (BOK) in Sukamara. Using multiple linear regression analysis (multiple regression analysis) with 63 respondents. The analysis showed that the dimensions of the company’s policy that includes: provision of salary or wages, the provision of facilities and incentives significant and positive impact on the morale and enthusiasm of employees at PT. Borneo Oil Kusuma (BOK) in Sukamara. While the dimensions of the company’s policy which includes: proper placement of employees and the work environment is not significant and positive impact on the morale and enthusiasm of employees at PT. Borneo Oil Kusuma (BOK) in Sukamara.